Russian Federation : Selected Issues. (IMF Staff Country Reports; Country Report ;, 2018)
This Selected Issues paper focuses on the Russian state's footprint in the economy. Available cross-country employment data suggests that the Russian state's is relatively large, like that of Scandinavian countries. In sectors where the state's share is high, economic concentration is larger, but concentration is large even in sectors where the state's share is low. Existing policies to protect and promote competition, including in state procurement, need to be strengthened. The IMF Staff estimates suggest that the state represented about one third of Russia's value added (VA) in 2016, smaller than in the mainstream narrative but nonetheless large. The Russian state represents close to 40 percent of formal sector activity and 50 percent of formal sector employment. State-owned-enterprises (SOE) are present in most sectors of activity. The state's share in VA was approximated by its share in sales for market activities, and by employment for nonmarket activities. SOEs appear to underperform relative to non-state firms in a variety of economic activities.